PERSPECTIVEs on supervised exercise programs in people with metastatic breast cancer: a qualitative study in four European countries - Depenbusch, Johanna; Sweegers, Maike; Aaronson, Neil K.; Wengström, Yvonne; Backman, Malin; Arraras, Juan I.; Schranz, Melanie; Büchler, Britta; Lachowicz, Milena; May, Anne M.; Steindorf, Karen; Stuiver, Martijn M. (Supportive care in cancer, 2023)
Supervised exercise is a potentially promising supportive care intervention for people with metastatic breast cancer (MBC), but research on the patients’ perspective is limited. The aim of the current focus group study was to gain an in-depth understanding of MBC patients’ perceived barriers, facilitators, and preferences for supervised exercise programs.
Gesehen am 04.08.2023